Regulasi Emosi yang Dilakukan Orang dengan Penyakit Lupus (odapus) - Ahyani Radhiani Fitri (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2009)
Mental health and physical health are fundamentally linked. People living with a physical illness are at greater possibility of experiencing a broad variety of psychological problems. This study aimed to study about Odapus' (person with Lupus) emotion regulation. There are two types of emotion regulations: cognitive reappraisal and expression suppression. Lupus is a chronic disease with multi-systemic disorder of autoimmune system which unknowable causes. The subjects were selected by a purposive sample technique and the data were collected by a semi-structured interview with open ended questions. The results revealed that subjects expressed selection situation, situation modification, intentional deployment, cognitive change, and response modulation. Transcendental relationship to God and family support as other emotion regulation forms were also revealed. Life experiences before, during, and after the diagnosis were related and resulted perspective and attituted toward Odapus. The result also suggests that social supports including physical, emotional, and instrumental supports, then, are necessary to support the efforts to achieve higher level of well being.Keywords: Emotion Regulations, Cognitive Reappraisal And Expression Suppression People With Lupus.